The Lebanese Pre-salt Oil and Gas Production Economic Challenges and Revenues - Taher, Hanadi (International Journal of Energy Economics and Policy, 2017)
This paper examines the challenges for oil and gas production and its influence on the Lebanese economy. Lebanese economy expected to become a new oil and gas producer starting 2020. The oil and gas exploration and production in Lebanon faces different challenges mainly fiscal inefficiency; oil plenty, Dutch disease phenomena, Nigerian disease and resource curse. Managing the oil and gas production process with a convenient fiscal regime adjustment would cause an efficient economic reform. The data are from International Monetary and Funds forecasted Lebanese economic data, Energy Information Administration forecasted oil, and gas international prices from 2017 to 2020. Based on the collected data beside our estimated scenarios for the annual oil and gas production capacity, the simulated sensitivity analysis showed a significant increase in the monetary value for the Lebanese oil and gas production and fiscal revenue although it varies according to the suggested scenarios. Keywords: gas and oil production in Lebanon, Lebanese oil and gas production challenges JEL Classifications: Q43; Q47